Application Of Game Theory In Determining Optimum Marketing Strategy In Marketplace - Intan Permata; Esther Sorta Mauli Nababan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
The trend of shopping in society is getting shifted, marked by the presence of the growing marketplaces and e-commerce. There are so many choices of marketplaces that can be easily accessed by the society. By the marketplaces vary, there would be many things to prepare by every marketplace to win the competition and always maintain the existence. Therefore, they must think and use the effective marketing strategy. The game theory is one of the ways that can be used to analyze the marketing strategy. The game theory is a mathematics model used in a conflict or competition among various interests that meet each other as competitors. Basically, the theory is a study of strategy interaction among the players to determine the best strategy and the obtained score. One of basic elements of the game theory is solving every case of the game theory where the pay-off matrix is shown in a game matrix table. The data of game between Shopee and Tokopedia obtained the optimum score which was 2.4443. Shopee and Bukalapak obtained the optimum score which was 6. Meanwhile, Tokopedia and Bukalapak obtained the optimum score which was 8.9925. In the Shopee, Tokopedia, and Bukalapak competition, the Nash equilibrium point is located at the point () with a pay off value (64,56,43), Shopee with a discount voucher strategy (), Tokopedia with a Product strategy (), and Bukalapak with a promotion strategy () which is the optimal strategy for each player.